BOOK REVIEW “DIARY OF AN INVASION, BY ANDREY KURKOV (2022)” - Machado, Renato (SÉCULO XXI: Revista de Relações Internacionais - ESPM, 2023)
Diary of An Invasion is a book written by Ukrainian author Andrey Kurkov in 2022. Written mostly during the first semester of 2022, the book is a chronological and personal diary that recounts Kurkov’s experience in Ukraine, during the initial months of the Russian invasion.